Optimal security design for risk-averse investors - Alex Gershkov; Benny Moldovanu; Philipp Strack; Mengxi Zhang (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We use the tools of mechanism design, combined with the theory of risk measures, to analyze how a cash constrained owner of an asset with known stochastic returns raises capital from a population of investors that differ in their risk aversion and budget constraints. The issuer partitions the asset's cash flow into several asset-backed securities, one for each type of investor. The optimal partition conforms to the commonly observed practice of tranching into senior debt, junior debt and equity. Tranching endogenously arises due to the differences in risk appetites among agents, and in the budget constraints they face.
Keywords: D82; G00; 330; Security Design; Risk Aversion; Tranching; Pooling